2016
DOI: 10.1172/jci86198
|View full text |Cite
|
Sign up to set email alerts
|

Persistent 7-tesla phase rim predicts poor outcome in new multiple sclerosis patient lesions

Abstract: BACKGROUND.In some active multiple sclerosis (MS) lesions, a strong immune reaction at the lesion edge may contain growth and thereby isolate the lesion from the surrounding parenchyma. Our previous studies suggest that this process involves opening of the blood-brain barrier in capillaries at the lesion edge, seen on MRI as centripetal contrast enhancement and a colocalized phase rim. We hypothesized that using these features to characterize early lesion evolution will allow in vivo tracking of tissue degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
318
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 250 publications
(354 citation statements)
references
References 57 publications
31
318
2
3
Order By: Relevance
“…A subset of chronic lesions, identified as chronic active or slowly expanding lesions have been described as having a rim of iron-enriched pro-inflammatory (M1) activated microglia/macrophages (m/M). 14 M1 microglia release cytotoxins to adjacent oligodendrocytes, 5 limit remyelination and contribute to further demyelination in chronic active lesions. 3 Therefore, identifying MS lesions with iron accumulation may be able to predict tissue damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of chronic lesions, identified as chronic active or slowly expanding lesions have been described as having a rim of iron-enriched pro-inflammatory (M1) activated microglia/macrophages (m/M). 14 M1 microglia release cytotoxins to adjacent oligodendrocytes, 5 limit remyelination and contribute to further demyelination in chronic active lesions. 3 Therefore, identifying MS lesions with iron accumulation may be able to predict tissue damage.…”
Section: Introductionmentioning
confidence: 99%
“…1, 3, 4, 79 Iron may be detected as hypointensity on T2 * weighted GRE magnitude image or its phase-enhanced version known as susceptibility weighted imaging (SWI). 8, 10 An R2 * (= 1/T2 * ) map computed from multi-echo GRE magnitude image can be used to estimate iron content.…”
Section: Introductionmentioning
confidence: 99%
“…112,130 The presence of iron is suggestive of microglia activity, and positive signal has been associated with chronic active MS lesions. 34,[131][132][133][134][135][136][137][138][139][140][141] Longitudinal QSM studies, conducted in our center, showed that lesion susceptibility increased as the lesion evolved from contrast enhanced to nonenhanced, indicating that it could be used as a biomarker. [142][143][144] All of these advanced magnetic resonance modalities require further validation in larger cohorts of patients and over a longitudinal time span.…”
Section: Introduction Of New Mri Sequences and Future Utilizationmentioning
confidence: 99%
“…5 As stated earlier, another important gain associated with 7T MRI is the ability of exploiting different mechanisms of contrast. Over the last few years, the characterization of iron as a tracer of MS pathology 1,6,7 was made possible by the use of susceptibility-based 7T MRI. The latter opened to the study of microglia activation in patients with MS and the in vivo identification of the so-called slowly expanding lesions, 1,6,7 till then characterized only pathologically.…”
mentioning
confidence: 99%
“…Over the last few years, the characterization of iron as a tracer of MS pathology 1,6,7 was made possible by the use of susceptibility-based 7T MRI. The latter opened to the study of microglia activation in patients with MS and the in vivo identification of the so-called slowly expanding lesions, 1,6,7 till then characterized only pathologically. 8 This new MRI approach will certainly change the way we measure Ultra-high-field (7.0 Tesla and above) MRI is now necessary to make the next step forward in understanding MS pathophysiology -YES F Bagnato and JC Gore MS disease progression and will extend the concept of disease activity beyond that of inflammation sustained by acute blood-brain barrier breakdown.…”
mentioning
confidence: 99%